Influencing Reduction in Meat Consumption through Social Marketing - Bogueva, Diana (Curtin University, 2017)
This thesis by publication comprises seven articles which explore the issues of reducing meat consumption and the contribution of social marketing in influencing behavioural change. Given the unprecedented and pressing need for the western world to acknowledge meat consumption as a main contributor to climate change and environmental deterioration, the thesis presents results from surveys conducted in Sydney and develops a new sustainability social marketing mix and model for encouraging dietary shifts away from meat.